Housing transitions through the life course : aspirations, needs and policy - Beer, Andrew; Faulkner, Debbie (Bristol, U.K. ; Portland, Or. : Policy Press, 2011)
Lifetime attitudes to housing have changed, with new population dynamics driving the market and a greater emphasis on consumption. This important contribution to the literature argues that how we think about households and their housing needs to be recast to acknowledge this changed environment and provide a more powerful conceptual framework.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Home ownership -- Government policy -- Australia; Housing policy -- Australia; Public housing -- Australia; Home ownership -- Government policy -- Great Britain; Housing policy -- Great Britain; Public housing -- Great Britain; Home ownership -- Government policy -- United States; Housing policy -- United States; Public housing -- United States